FRUIT AND VEGETABLE GROWING IN BULUNG'UR DISTRICT ABOUT CLUSTERS IN THE DIRECTION DIRECTORY - Akhmedova Mukhayyo (Journal of new century innovations, 2022)
A total of 2 fruit and vegetable farms, 1 grain farm, 1 potato farm and 5 grape farms have been established and are operating in Bulung'ur district of Samarkand region. The fruit and vegetable agrocluster of "BULUNG'UR SANDVIK" LLC was formalized as a cluster by the decision of the district governor No. 1738-Q dated August 8, 2018, including a total of 346 hectares from the agrofirms of Uzbekistan, Mingchinor, Ulug'bek, A. Makhsumov and Beshkuvi in the district, of which 342 are used. 33 hectares of land area has been allocated for vegetable production based on a long-term lease agreement.